Unconventional Computation 9th International Conference, US 2010, Tokyo, Japan, June 21-25, 2010. Proceedings - Calude, Cristian S.; Hagiya, Masami; Morita, Kenichi; Rozenberg, Grzegorz; Timmis, Jon.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 9th International Conference on Unconventional Computation, UC 2010, held in Tokyo, Japan, in June 2010. The 15 revised full papers presented together with 4 extended abstracts of invited talks, and 8 abstracts of posters were carefully reviewed and selected from numerous submissions. The papers are devoted to all aspects of unconventional computation --- theory as well as experiments and applications. Typical topics are: natural computing including quantum, cellular, molecular, membrane, neural, and evolutionary computing, as well as chaos and dynamical system-based computing, and various proposals for computational mechanisms that go beyond the Turing model.
Invited Talks -- Computations Inspired from the Brain -- Algebras and Languages for Molecular Programming -- A Computational Journey into Nonlinearity -- Computable Scientists, Uncomputable World -- Regular Contributions -- Finite State Transducers with Intuition -- Reversibility and Determinism in Sequential Multiset Rewriting -- Synchronization in P Modules -- On Universality of Radius 1/2 Number-Conserving Cellular Automata -- DNA Origami as Self-assembling Circuit Boards -- Tug-of-War Model for Multi-armed Bandit Problem -- Characterising Enzymes for Information Processing: Towards an Artificial Experimenter -- Majority Adder Implementation by Competing Patterns in Life-Like Rule B2/S2345 -- Solving Partial Differential Equation via Stochastic Process -- Postselection Finite Quantum Automata -- A New Representation of Chaitin ? Number Based on Compressible Strings -- Quantum Query Algorithms for Conjunctions -- Universal Continuous Variable Quantum Computation in the Micromaser -- Quantum Computation with Devices Whose Contents Are Never Read -- The Extended Glider-Eater Machine in the Spiral Rule -- Posters -- Formalizing the Behavior of Biological Processes with Mobility -- Quantum Finite State Automata over Infinite Words -- A Geometrical Allosteric DNA Switch -- Properties of (3z(BPlanar Binary (Butchi Number)(3y (B-- Characterising Enzymes for Information Processing: Microfluidics for Autonomous Experimentation -- Inference with DNA Molecules -- A Network-Based Computational Model with Learning -- Image Processing with Neuron-Like Branching Elements (POSTER).s
Keywords: Computer science; Computer software; Logic design; Artificial intelligence; Bioinformatics; Computer Science; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Mathematical Logic and Formal Languages; Artificial Intelligence (incl. Robotics).; Logics and Meanings of Programs; Computational Biology/Bioinformatics.